8y+4(4y-2)+5=45

Simple and best practice solution for 8y+4(4y-2)+5=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y+4(4y-2)+5=45 equation:


Simplifying
8y + 4(4y + -2) + 5 = 45

Reorder the terms:
8y + 4(-2 + 4y) + 5 = 45
8y + (-2 * 4 + 4y * 4) + 5 = 45
8y + (-8 + 16y) + 5 = 45

Reorder the terms:
-8 + 5 + 8y + 16y = 45

Combine like terms: -8 + 5 = -3
-3 + 8y + 16y = 45

Combine like terms: 8y + 16y = 24y
-3 + 24y = 45

Solving
-3 + 24y = 45

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 24y = 45 + 3

Combine like terms: -3 + 3 = 0
0 + 24y = 45 + 3
24y = 45 + 3

Combine like terms: 45 + 3 = 48
24y = 48

Divide each side by '24'.
y = 2

Simplifying
y = 2

See similar equations:

| 7/10x=103/20 | | 11x^9y^2/66x^2y^7 | | 750+0.03x=1200 | | 5x-3=43 | | X^2-5x+10=-4 | | 7/10x-5=13/20 | | 5(n+7)-15=45 | | x-3=x+18 | | 2m^3+9m^2+12m+5=0 | | -7(-6-3p)+10=115 | | 80x/360 | | 5+30x=15x+41 | | 6.4=1.2[4+2x] | | 7x-3x+2=2x+2x+8-6 | | 7(3x+2)-3=2(x-2)+5 | | (3p-7)(2p+8)= | | 10x+6=-7 | | 2[3x+4]=19 | | 4n+1=36 | | 0.26x+0.07(60000-x)=11040 | | 0=5x^(2/3)-2x^(5/3) | | -2-5x+2= | | 1/2[5-x]=1/4 | | -2xy^2(3x-2y)= | | 7z-6=5 | | x^3-8x+8=0 | | 10x-5=x+8 | | 9^-5x^4/9^-3x^-1= | | 7(u-6)=-7 | | 5x-3x-24=8x-2x+24 | | 43/29=24/x | | =32-[9-3(4-10)]+(2-5)3 |

Equations solver categories